Emotional and Social Drivers of Consumer Behaviour in Live-Streaming Commerce: A Conceptual Integration of PAD and SOR Models - Zul Fahmi; Vidyarini Dwita; Yunia Wardi; Abror Abror; Dina Patrisia; Teh Nurul Afiza Abdul Jalil (Jurnal Maksipreneur, 2026)
Live-streaming commerce has reshaped digital retail by integrating real-time interaction and immersive social environments that drive emotional responses and stimulate impulsive buying. Although the Stimulus–Organism–Response (SOR) framework and the Pleasure–Arousal–Dominance (PAD) model have been frequently applied in previous studies, their integration receives little attention, and the dominance dimension is often overlooked. Therefore, this study systematically maps the intellectual structure and thematic evolution of research to examine the relationships between social presence, affective states, and impulsive buying in live-streaming commerce. Using a bibliometric-based systematic literature review, 998 articles published between 2021 and 2026 were retrieved through Publish or Perish and Google Scholar. From this pool, 18 Scopus-indexed business and management studies were chosen as they met the PRISMA inclusion criteria. VOSviewer analysis reveals a strong empirical concentration on pleasure and arousal as primary mediating mechanisms, while the dominance is noticeably under-explored and the integration of SOR is often incomplete. This study enhances the PAD–SOR framework by demonstrating how the interplay between emotional arousal and emotion regulation influences impulsive purchasing in immersive digital commerce.